Obliged parties in the EU regulation on artificial intelligence - Barrio Andrés, Moisés (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The EU AI Act sets unprecedented regulatory challenges for all categories of market players. How the AI Act will affect entities depends on a number of factors, such as the type of entity, possible changes to the AI system, exclusions, prohibitions and so on. This article focuses on the question of who the actual addressees of the obligations are and how entities - whether private or public - can establish with certainty which categories of obligations apply to them.
Keywords: Artificial intelligence; EU Regulation on artificial intelligence; Regulation (EU) 2024/1689; AI Act; Digital law